Thermal performance of entropy-optimized tri-hybrid nanofluid flow within the context of two distinct non-newtonian models: Application of solar-powered residential buildings - Khashi’ie, Najiyah Safwa; Galal, Ahmed Mohamed; Obalalu, Adebowale Martins; Akindele, Akintayo Oladimeji; Khan, Umair; Usman, Abdulazeez Adebayo; Olayemi, Olalekan Adebayo (Tech Science Press, 2025)
The need for efficient thermal energy systems has gained significant attention due to the growing global concern about renewable energy resources, particularly in residential buildings. One of the biggest challenges in this area is capturing and converting solar energy at maximum efficiency. This requires the use of strong materials and advanced fluids to enhance conversion efficiency while minimizing energy losses. Despite extensive research on thermal energy systems, there remains a limited understanding of how the combined effects of thermal radiation, irreversibility processes, and advanced heat flux models contribute to optimizing solar power performance in residential applications. Addressing these knowledge gaps is critical for advancing the design and implementation of highly efficient thermal energy systems. Owing to its usage, this study investigates the thermal energy and irreversibility processes in the context of solar power systems for residential buildings. Specifically, it explores the influence of thermal radiation and the Cattaneo–Christov heat flux model, considering the interactions over a stretching surface. The study incorporates cross fluid and Maxwell fluid effects into the governing model equations. Utilizing the Galerkin-weighted residual method, the transformed model is solved to understand the impacts on heat distribution. The findings reveal that increased thermal radiation and thermal conductivity significantly enhance heat distribution, offering valuable insights for optimizing solar power system efficiency in residential applications.